The Golden Age of Cataclysmic Variables and Related Objects - II Concluding Address - F. Giovannelli (Acta Polytechnica CTU Proceedings)
Before to conclude officially this workshop — far from me the idea to attempt some concluding remarks already dealt at the meeting with various burning by Joseph Patterson, Mariko Kato, Dmitry Bisikalo, and Rene Hudec —, I would like to comment few highlights coming out from our fruitful week of discussions about The Golden Age of Cataclysmic Variables and Related Objects - II, without any pretension of completeness.